2D ferroelectric AgInP2Se6 for Ultra‐Steep Slope Transistor with SS Below 10 mV Decade−1 - Yujue Yang; Zihao Liu; Xueting Liu; Huafeng Dong; Xin Zhang; Juehan Yang; Fugen Wu; Jingbo Li; Nengjie Huo (Advanced Electronic Materials)
Abstract Along with continuous size shrinking, conventional silicon based transistors face the the challenges of both manufacture complexity and physical limitations. The negative capacitance transistors (NC‐FETs) using 2D ferroelectric materials as dielectric insulators are emerging as reliable solutions owing to their advantages of breaking the Boltzmann limitation and Complementary Metal‐Oxide Semiconductor (CMOS) compatibility. Here, the room temperature ferroelectricity of 2D AgInP2Se6 is discovered which is further integrated with MoS2 channel into ultra‐steep NC‐FETs for low‐power electronic applications. Due to the negative capacitance effect of AgInP2Se6 during the polarization reversal process, the transistor breaks the Boltzmann limitation with a subthreshold swing (SS) of less than 10 mV decade−1. By optimizing the thickness of AgInP2Se6, superior transistor performance with a minimum SS of 7.75 mV dec−1 and a high on/off ratio of up to 5.88 × 104 can be achieved. This work develops a new 2D ferroelectric AgInP2Se6 with room temperature ferroelectricity, providing promising material platforms for small‐size, ultra‐steep, and low‐power electronics.